Patient-Reported and Performance Outcomes Significantly Improved in Elderly Patients with Vestibular Impairment following Rehabilitation: A Retrospective Study - Daniel Héctor Verdecchia; Agustina Maria Monzón; Valentina Urbina Jaimes; Fernando Rocha Oliveira; Laércio da Silva Paiva; Tatiana Dias de Carvalho (Journal of Aging Research)
Objective. To describe the results of a vestibular rehabilitation (VR) program in the timed up and go (TUG), gait speed (GS), and dizziness handicap inventory (DHI) scores for elderly vestibular patients in a developing country. Methods. Descriptive study with retrospective data collected from the clinical records of vestibular patients. The following information was recorded: sex, age, type of vestibular disorder, DHI score, and performance in TUG and GS, before and after participation in a VR program taking place from January 1 to August 30, 2017. The VR program consisted of 10 twice weekly sessions in the clinic and daily exercises at the patient’s home. We used Student’s t-test for paired and Wilcoxon’s test according to the data distribution. The level of significance was 5%. Results. Data from 57 patients (49 females; 78 ± 5.8 years old) were used. There were statistically significant differences in TUG (12.52 versus 11.56), GS (0.81 versus 0.90 m/s), DHI total handicap (46 versus 24), physical (14 versus 8), emotional (14 versus 6), and functional (18 versus 12) domains. Conclusion. The functional outcome measures reported, including TUG, gait speed, and DHI, reflect statistically significant improvements in elderly patients after vestibular rehabilitation; the DHI improvements are clinically relevant.